Learner Attribution To Performance In A Pretest Of Writing In English - Attan, Anie; Mohamed Zin, Zuhana (Universiti Sains Malaysia, 2016)
Many universities cap a minimum of IELTS Band 6 proficiency on potential postgraduate students as benchmark of required proficiency to pursue postgraduate studies. For the many who failed to meet this requirement, a review of their performance with a match of attribution causal factors is one avenue to establish their failure to meet the requirement. This paper addresses that issue with the aim of identifying the causal factors, both internal and external for non-achievement of targeted score through a case study of five Association of South East Asian Nations (ASEAN) scholars intending to pursue postgraduate studies in a university in Malaysia. A sample IELTS Test of Writing was administered and rated according to IELTS test requirements. The subjects then responded to a questionnaire, rated on a 4-point Likert scale, eliciting their attribution towards language learning and achievement. Descriptive statistics were used in data analysis. Findings indicate that all five participants did not meet the IELTS minimum requirement. A match of attribution items with non-achievement showed the internal factor rather than the external, being the cause for non-achievement..